PELATIHAN EMERGENCY RESPON TIME DI INSTALASI GAWAT DARURAT RSUD DR. R. KOESMA TUBAN - Miftahul Munir; Muhammad Sudrajad; Adibah Enggar; Didik Suharsoyo; Surotul Ilmiah (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2022)
Response time which can cause physical disability and death in patients, the speed in this case is an action with less than 5 minutes from the patient's arrival at Emergency departments, indirectly experience and education may be related to the length of response time.This research uses analytic survey research design with cross sectional time approach. Respondents in this studyare all nurses at the RSUD Dr. R. Koesma Tuban were 23 nurses, the technique used in the study was total sampling. The independent variable in this study is work experience and nurse education while the dependent variable is the response time for patient care. The instrument used was a questionnaire, and the analysis of this study used the Pearson correlation test.Statistical test results on work experience variables with response time obtained Sig (2-tailed) of 0.04 less than 0.05 then there is a correlation, while for the education level variable obtained Sig (2-tailed) 0.58 greater than 0.05 then it does not have a correlation to response time.So it can be concluded from the results of statistical tests there is a relationship of work experience with the response time of handling patients and the level of education has no relationship with response time. Keywords : Work experience, Nurse Education, Response Time for Patient Handling